Spirituality, Healing and Indigenous Knowledge in Herbal Medicine: A Case of the Ndrukpa Ethnic Minority in Uganda - Agatha, Alidri; Owinjrwoth, Chanikakare Gerald (East African Journal of Traditions, Culture and Religion, 2025)
This paper explores spirituality, healing and Indigenous knowledge in herbal medicine practices among the Ndrukpa ethnic minority community of the West Nile region in Uganda, and how they influence their thought processes and worldviews. The Critical theory and post-colonial theory are adopted to integrate indigeneity and hybridity. The field study was conducted from 2022 to 2025 to document the history of the Ndrukpa people whose history had remained undocumented and kept in memory. The qualitative approach and ethnohistorical design were used to explore the socio-cultural history of the people. The key emergent themes include: spirituality, healing, indigenous knowledge in herbal medicine, religious rituals and sacrifices, apprenticeship, belief system, belief in God the creator, gods, spirits and living dead and the living, magic, sorcery and divine retribution, and identity. Spirituality was a critical component of Ndrukpa and was holistically viewed for its social, economic, political and cultural importance. The Ndrukpa believe in the relationship between spirituality and the natural environment, and the critical role artefacts play in spirituality. Ndrukpa ritual and its practitioners exhibited connections in relation to space, performance and perception. Ndrukpa believed in healing rituals and viewed healing holistically as physical, emotional, intellectual, social, and spiritual aspects of human experience. Treatment, healing, and spirituality were to restore health and wellbeing. Indigenous healing systems are linked to a permanent presence of ancestral forces without a time limit. The use of indigeneity and hybridity in spirituality, healing and indigenous knowledge in medicine is not to romanticize culture and spirituality but rather view them as a promotion of the notion ‘African solution to African problem’ and a strategy for the development of structured and informed by local knowledge, resources and identities.